Brain Natriuretic Peptide Is a Powerful Predictor of Outcome in Stroke Patients with Atrial Fibrillation - Kenji Maruyama; Shinichiro Uchiyama; Tsuyoshi Shiga; Mutsumi Iijima; Kentaro Ishizuka; Takao Hoshino; Kazuo Kitagawa (Cerebrovascular Diseases Extra, 2017)
Background: Since stroke patients with nonvalvular atrial fibrillation (NVAF) have poor outcomes in general, the prediction of outcomes following discharge is of utmost concern for these patients. We previously reported that brain natriuretic peptide (BNP) levels were significantly higher in NVAF patients with larger infarcts, higher modified Rankin Scale (mRS) score, and higher CHADS2 score. In the present study, we evaluated an array of variables, including BNP, in order to determine significant predictors for functional outcome in patients with NVAF after acute ischemic stroke (AIS). Methods: A total of 615 consecutive patients with AIS within 48 h of symptom onset, admitted to our hospital between April 2010 and October 2015, were retrospectively searched. Among these patients, we enrolled consecutive patients with NVAF. We evaluated the mRS score 3 months after onset of stroke and investigated associations between mRS score and the following clinical and echocardiographic variables. Categorical variables included male sex, current smoking, alcohol intake, hypertension, diabetes mellitus, dyslipidemia, coronary artery disease, peripheral artery disease, use of antiplatelet drugs, anticoagulants, or tissue plasminogen activator (tPA), and infarct size. Continuous variables included age, systolic blood pressure (SBP), diastolic blood pressure, hemoglobin, creatinine, D-dimer, brain natriuretic peptide (BNP), left atrial diameter, left ventricular ejection fraction (EF), and early mitral inflow velocity/diastolic mitral annular velocity (E/e’). We also analyzed the association of prestroke CHADS2, CHA2DS2-VASc, and R2CHADS2 scores, and National Institutes of Health Stroke Scale (NIHSS) score on admission with mRS score 3 months after the onset of stroke. Patients were classified into 2 groups according to mRS score: an mRS score ≤2 was defined as good outcome, an mRS score ≥3 was defined as poor outcome. To clarify the correlations between categorical or continuous variables and mRS score, uni- and multivariate logistic regression models using the stepwise variable selection method were applied. Results: Among 157 patients with NVAF after AIS, 63.7% were male and the mean age was 75.9 years. In univariate regression analysis, poor outcome (mRS score ≥3) was associated with use of tPA, infarct size, age, SBP, BNP, EF, and NIHSS score. In multivariate regression analysis, BNP levels (odds ratio [OR] 6.40; 95% confidence interval [CI] 1.26–32.43; p = 0.0235) and NIHSS score (OR 2.87; 95% CI 1.84–4.47; p < 0.001) were significantly associated with poor outcome (mRS score ≥3) after adjusting for use of tPA, infarct size, age, BNP, EF, and NIHSS score. Conclusions: Apart from NIHSS score, BNP was a very useful predictor for long-term outcomes of patients with NVAF after AIS.